Rancang Bangun Greenhouse Hidroponik Deep Water Culture (DWC) Dengan Sistem Monitoring Berbasis Internet of Things (IoT) - Samuel Purba; Herry F. Pinatik; Dedie Tooy (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2026)
The objectives of this study are (1) To design and build a household-scale Deep Water Culture (DWC) hydroponic greenhouse with an IoT-based monitoring system to monitor environmental and hydroponic DWC parameters in supporting urban farming on narrow land. (2) To test the performance of the IoT-based DWC hydroponic greenhouse monitoring system including: a) monitoring temperature, humidity using a DHT22 sensor, b) nutrition using a TDS gravity sensor, c) water level using a water level sensor and a 5V pump, d) light intensity (lux) digitally. This study uses the Research and Development (R&D) method, namely designing, building and testing a monitoring system on an IoT-based DWC hydroponic greenhouse. The system successfully conducted testing by monitoring for three days on the DWC hydroponic greenhouse. The temperature inside the greenhouse ranged from 29.6-46.4 °C with a humidity of 43.9-85%, while the temperature outside the greenhouse ranged from 26.2-39.7 °C with a humidity of 53.6-95%. These conditions indicate that the greenhouse has a higher temperature and tends to have lower humidity. The high temperature increase and low humidity are due to the greenhouse effect and limited air circulation. The nutrient value ranges from 603-619 ppm, with an accuracy of 96.25%. The water level is 10 cm, but the sensor reads 8-9 cm with an error of 10-20%. Light intensity ranges from 13,840 to 140,600 lux. In conclusion, the IoT-based monitoring system is capable of performing well in monitoring environmental parameters in real-time, and regular maintenance is necessary to improve sensor accuracy.